The Effectiveness of Autograft Used in Anterior Cruciate Ligament Reconstruction of the Knee: Surgical Records for the New Generations of Orthopedic Surgeons and Synthetic Graft Revisit - Bashaireh KM; Audat Z; Radaideh AM; Aleshawi AJ (Orthopedic Research and Reviews, 2020)
Khaldoon M Bashaireh,1 Ziad Audat,1 Ahmad M Radaideh,1 Abdelwahab J Aleshawi2 1Department of Special Surgery, Division of Orthopedics, Faculty of Medicine, Jordan University of Science and Technology, Irbid 22110, Jordan; 2Faculty of Medicine, Jordan University of Science and Technology, Irbid 22110, JordanCorrespondence: Khaldoon M BashairehDepartment of Special Surgery, Division of Orthopedics, Faculty of Medicine, Jordan University of Science and Technology, P. O. Box 3030, Irbid 22110, JordanTel +962799051087Fax +962 2 7201064Email bashaireh@just.edu.joObjective: In this article, we aim to revisit the synthetic graft and review the advantages and disadvantages between different types of grafts for patients who underwent anterior cruciate ligament (ACL) reconstruction in a tertiary medical institute for the new generations of surgeons.Patients and Methods: Retrospectively, we identified 115 patients who underwent arthroscopic ACL reconstruction between 2006 and 2009. We were able to retrieve 74 patients from them. The 74 patients were divided into 32 patients who underwent primary arthroscopic ACL reconstruction with hamstring and patellar tendon autograft and 42 cases with an active biosynthetic composite (ABC) ligament. The mean the follow-up period for both groups was 7 years. The following information was obtained: standard demographic information (age, sex), clinical presentation, presence of trauma, associated injuries, types of grafts (autograft versus synthetic graft) and postoperative complications. Moreover, functional and clinical outcomes in addition to the satisfaction of patients using the international knee documentation committee (IKDC) score and knee injury and osteoarthritis outcome score (KOOS) were measured.Results: We found that the natural (autograft) was better in terms of clinical and functional outcome than the synthetic one (the scores of KOOS and IKDC were better in natural grafts). Furthermore, the immediate postoperative results for the pivot and Lachman tests were better in natural grafts. On the other hand, the rate of re-rupture was similar for both groups. However, the long-term inflammatory changes and stiffness that is attributed to the immunological reactions were more in the synthetic grafts.Conclusion: This study revisited the synthetic graft and provided evidence that the natural grafts are more beneficial with less complications, as they had better immediate and long-term postoperative clinical and functional outcomes. We recommend the utilization of autograft as first choice and the synthetic not to be used given the current criteria.Keywords: anterior cruciate ligament (ACL), arthroscopy, autologous, knee